Cloud-Native Security in Informatics: A Bibliometric Analysis of Emerging Research - Loso Judijanto; Arnes Yuli Vandika (Westscience Press, 2026)
Fast development of cloud computing technologies has led to the emergence of cloud-native architecture, which created both new possibilities and challenges in the area of informatics, in particular cybersecurity. Being a set of flexible and scalable cloud-native technologies, such as containers, microservices, Kubernetes and DevOps, cloud-native environments imply complex security risks, such as data protection, network, identity and dynamic infrastructure management. The purpose of this study is to investigate the evolution, scientific structure and future research directions in cloud-native security by means of bibliometric approach. Academic publications were identified within relevant databases and analyzed by means of VOSviewer software to uncover trends in publications, co-occurrence of keywords, citation structures, authors' collaborations and international scientific networks. The results show that cloud-native security research started from basic issues, such as cloud computing, network security, and container technologies to develop into more sophisticated areas, such as DevSecOps, automation, artificial intelligence, anomaly detection, intrusion detection and intelligent cybersecurity systems. The analysis also indicates that the United States has a dominant role in global research contributions, supported by strong collaborations with countries such as India, the United Kingdom, Italy, France, and South Korea. Highly cited studies demonstrate that current research priorities focus on secure cloud architectures, serverless computing, cloud-native observability, container isolation, and autonomous security management. This study provides a comprehensive understanding of the research landscape and highlights future directions toward AI-driven security frameworks, zero-trust architectures, and automated defense mechanisms for resilient cloud-native ecosystems.